Timing and Determinants of Tuberculosis Treatment Interruption in Nairobi County, Kenya - Violet Jepchumba; Simon Karanja; Evans Amukoye; Lawrence Muthami; Hillary Kipruto (International Journal of Public Health Science (IJPHS), 2017)
Tuberculosis (TB) treatment is a key pillar in the management and control of TB. Service delivery within the treatment facilities plays an important role in ensuring treatment adherence by TB patients. A prospective cohort study involving 25 health facilities, 25 facility in-charge officers and 291 patients diagnosed as new sputum smear positive (SM+) between December 2014 and July 2015 was undertaken. The aim of the study was to estimate the median time to treatment interruption, associated factors and overall predictors of non-adherence to TB treatment. A total of 19 (6.5%) treatment interruptions were observed. The median time to default was 56 [95% CI, 36-105] days. Treatment in a non-public facility [AOR=0.210, 95% CI (0.046-0.952)] and facilities perceived to have adequate number of health care workers to offer Directly Observed Therapy (DOT) [AOR=0.195, 95% CI (0.068-0.56)] showed a lower odds of treatment interruption whereas attainment of secondary level education [AOR=5.28, 95% CI (1.18-23.59)] indicated a higher odds of treatment interruption. Non-clinical aspects of health care service delivery influence patient adherence to TB treatment. Health seeking behavior of groups considered to be high risk for treatment interruption should be incorporated into the design and delivery of TB treatment.